Currículo desde una perspectiva cultural de la comunidad Zenú en el área de Ciencias Naturales - Acosta-Meza, David De jesus (Revista Científica, 2016)
Design curriculum from a cultural perspective Zenú community in the area of Natural Sciences and Environmental Education emerges as through the design of a curriculum at Zenú ethnicity teaching of natural sciences potentiates and also the study of ancestral knowledge of this community and cultural identity. Therefore, the objective of designing a curriculum from the natural sciences to generate new knowledge, responding to the interests and needs of ethnicity, and educational institutions, framed this in an endogenous education system, rescuing their worldview and contrasting curricula raised schools to evaluate the work of the indigenous component in education that young people receive. Analyzing the importance of working contextualized curricula that prioritize the needs, taking into account the knowledge present in the community giving participation to community agencies, to identify themselves and that is the same population that have the ability to intervene from different areas education, which are not restricted in school generated contrast and evaluation of old curricula and transformation of these best looking quality of life of this population. This research is designed under the criteria of ethnographic research, qualitative approach. Obtaining detailed descriptions of situations, events, people, interactions and behaviors that are observable, presenting a curriculum from ancestral knowledge, based on the collected and analyzed information in the educational context.